Perceptions of Saudi parents of students with autism toward the responsibilities of transition plan members in implementing transition plans - Salman Almughyiri (PLoS ONE, 2026)
Objective This study investigates how Saudi parents of children with autism perceive the roles and responsibilities of school staff and families in implementing transition plans. It looks at how these duties are shared between home and school during the planning phase. Methods A cross-sectional, quantitative approach was employed. A total of 469 parents of students with autism from the Riyadh (n = 243) and Makkah (n = 226) regions completed a structured survey. The instrument, developed from validated measures and based on the National Technical Assistance Center on Transition (NTACT) practices, used a 5-point Likert scale. Descriptive and inferential statistics (t-tests and cross-tabulations) were applied to compare perceptions across demographic variables such as gender, education level, and region. Results Parents viewed schools as more responsible than homes for most transitional skills, especially in areas like self-advocacy, vocational preparation, and study skills. Conversely, daily living and independent living skills were more often considered the family’s responsibility. Perceptions did not significantly differ based on gender, education, or location. Conclusion The results indicate a collaborative responsibility between families and schools, with schools being considered the primary partner in most skill areas. To support smooth transitions for individuals with autism, increased collaboration between educators and families and parent-led training are essential.